An Expertise-Oriented Evaluation of the Center for Entrepreneurship Development and Vocational Studies, Federal Polytechnic, Ado-Ekiti, Nigeria: Implications for Assessing and Improving the Federal Polytechnic System in Nigeria - Matt Baker; Mike Bassey; Engr A.A Jimoh; Taiwo Akande (Journal of International Agricultural and Extension Education, 2015)
An on-campus evaluative study was conducted at Federal Polytechnic’s Center for Entrepreneurship Development and Vocational Studies in Ado-Ekiti, Ekiti State, Nigeria. One of the evaluation objectives was to conduct an intensive on-site program review. Both quantitative and qualitative program-related data were assessed and a process evaluation was conducted. The aquaculture skills enterprise area was in highest demand by full-time students in both diploma programs, while soap making was in highest demand by part-time students. Data revealed that students scored highest on their final exam in the fourth-year skills training course (Practical Skills Training) and lowest in the first year theory course (Introduction to Entrepreneurship). Federal Polytechnic offers a National Diploma and a Higher National Diploma program. The Entrepreneurship Education program offered by the Center is core requirement of every student regardless of major. Students enroll in a theory course followed by a skills acquisition or laboratory course each academic year. Skills acquisition courses are offered in 15 small-business enterprise areas. A number of themes emerged from the qualitative data regarding the curriculum and program management and operations. The authors conclude with a process-based critique of the program review, with implications for future reviews in the Federal Polytechnic system. The Entrepreneurship Education program is in its fourth year and is considered a flagship program by national experts in Nigeria
Keywords: academic program reviews; post-secondary education; technical education; tertiary education; federal polytechnics